Breathomics for Assessing the Effects of Treatment and Withdrawal With Inhaled Beclomethasone/Formoterol in Patients With COPD - Montuschi, Paolo; Santini, Giuseppe; Mores, Nadia; Vignoli, Alessia; Macagno, Francesco; Shoreh, Rugia; Tenori, Leonardo; Zini, Gina; Fuso, Leonello; Mondino, Chiara; Di Natale, Corrado; D'Amico, Arnaldo; et al. (Frontiers in Pharmacology, 2018)
Background Prospective pharmacological studies on breathomic profiles in COPD patients have not previously reported. We assessed the effects of treatment and withdrawal of an extrafine inhaled corticosteroid (ICS)-long-acting β2-agonist (LABA) fixed dose combination (FDC) using a multidimensional classification model including breathomics. Methods A pilot, proof-of-concept, pharmacological study was undertaken in 14 COPD patients on maintenance treatment with inhaled fluticasone propionate/salmeterol (500/50 μg b.i.d.) for at least 8 weeks (visit 1). Patients received 2-week treatment with inhaled beclomethasone dipropionate/formoterol (100/6 μg b.i.d.) (visit 2), 4-week treatment with formoterol alone (6 μg b.i.d.) (visit 3), and 4-week treatment with beclomethasone/formoterol (100/6 μg b.i.d.) (visit 4). Exhaled breath analysis with two e-noses, based on different technologies, and exhaled breath condensate (EBC) NMR-based metabolomics were performed. Sputum cell counts, sputum supernatant and EBC prostaglandin E2 (PGE2) and 15-F2t-isoprostane, fraction of exhaled nitric oxide, and spirometry were measured. Results Compared with formoterol alone, EBC acetate and sputum PGE2, reflecting airway inflammation, were reduced after 4-week beclomethasone/formoterol. Three independent breathomics techniques showed that extrafine beclomethasone/formoterol short-term treatment was associated with different breathprints compared with regular fluticasone propionate/salmeterol. Either ICS/LABA FDC versus formoterol alone was associated with increased pre-bronchodilator FEF25%-75% and FEV1/FVC (P = 0.008-0.029). The multidimensional model distinguished fluticasone propionate/salmeterol versus beclomethasone/formoterol, fluticasone propionate/salmeterol versus formoterol, and formoterol versus beclomethasone/formoterol (accuracy > 70%, P < 0.01). Conclusions Breathomics could be used for assessing ICS treatment and withdrawal in COPD patients. Large, controlled, prospective pharmacological trials are required to clarify the biological implications of breathomics changes.